Encounters with Islam: studies in the anthropology of Muslim cultures - Rosen, Lawrence (Cambridge University Press, 2023)
"Exploring political, economic, and social encounters within and with the Muslim world across the eras, Lawrence Rosen develops a vibrant, nuanced portrait of the Islamic world that challenges existing stereotypes. Using a diverse range of illustrative case studies, Rosen draws previously unseen linkages across time, regions, and cultures"--